ASSESSMENT OF ANISOMETROPIA IN VISUALLY IMPAIRED CHILDREN AGED 6-14 YEARS IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess the prevalence and characteristics of anisometropia in children aged 6-14 years with visual impairment in Ho Chi Minh City.Subjects and methods: A retrospective descriptive study was conducted on 3593 visually impaired children aged 6-14 years in Ho Chi Minh City from August 2023 to October 2023.Results: The prevalence of anisometropia was 26.30%, with 23.60% showing a refractive difference between 1.00D and 3.00D. The rate of amblyopia was higher in all asymmetric refractions from 1.00D and above. Primary school children had a significantly lower prevalence of anisometropia (18.70%) compared to secondary school children (30.96%). The prevalence of unilateral refractive error was higher than that of bilateral refractive error.Conclusions: The prevalence of anisometropia in visually impaired children aged 6–14 years in Ho Chi Minh City was 26.30%. There were statistically significant correlations between anisometropia and amblyopia, school level, and the laterality of refractive error.